Integrated flexible zinc ion battery and preparation method and application thereof
By using a crosslinked acrylamide/N-hydroxymethylacrylamide copolymer network to eliminate the hierarchical interface of the flexible zinc ion battery, forming a fully integrated structure, solving the stability problem of the flexible zinc ion battery in the bending and twisting state, and significantly improving its deformation resistance and electrochemical properties.
Patent Information
- Application Number
- CN202510117360.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-22
AI Technical Summary
The existing flexible zinc ion batteries have insufficient ability to stably output electrical energy in long-term bending and twisting states, resulting in low energy density and poor deformation resistance, limiting their application in new flexible and wearable electronic devices.
Acrylamide/N-hydroxymethylacrylamide copolymer is used as the matrix material, and free radical copolymerization is carried out through initiators to form a cross-linking network, eliminating the original hierarchical interface, and strengthening the interface between the electrode layer and the electrolyte layer to form a fully integrated structure.
The stability of the zinc ion battery in the bending and twisting deformation at large angles and long-term bending and twisting is achieved, and the interface debonding and disassembly are avoided, which significantly improves deformation resistance and electrochemical properties.
Smart Images

Figure HDA0005258132930000011 
Figure HDA0005258132930000012 
Figure HDA0005258132930000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to energy storage, and in particular to an integrated flexible zinc ion battery and a preparation method and application thereof. Background Art
[0002] The emergence of new flexible and wearable electronic devices (flexible displays, wearable sensors, electronic skin, etc.) has greatly promoted the rapid development of flexible zinc-ion batteries that can power them. The development of high-performance flexible zinc-ion batteries has become a hot issue. Flexible zinc-ion batteries should have the ability to stably output electrical energy under long-term bending and twisting conditions. At present, classic flexible zinc-ion batteries usually include flexible electrode materials and electrolytes that can serve as both positive and negative electrodes. They are assembled and prepared by stacking flexible electrode materials, electrolytes and flexible electrode materials layer by layer to form an electrode|electrolyte|electrode sandwich structure. Moreover, flexible zinc-ion batteries currently usually use heterogeneous matrices to construct positive electrode / electrolyte / negative electrode, and there is an obvious interface between the three. Different positive electrode / electrolyte / negative electrode matrices and low interfacial compatibility will reduce the actual contact area between the positive electrode and the negative electrode and the electrolyte, thereby increasing the interfacial contact resistance and ultimately reducing the energy density; the interface interaction between the heterogeneous matrices of positive electrode / electrolyte / negative electrode is weak and only relies on the van der Waals force, the interface bonding is poor and the deformation amount is inconsistent, resulting in poor stability of the positive electrode / electrolyte / negative electrode interface, and ultimately poor deformation resistance. Therefore, the actual output energy density of flexible zinc-ion batteries is low, and the electrode|electrolyte|electrode sandwich structure will inevitably undergo relative displacement and interface delamination under repeated deformation, causing the flexible zinc-ion battery to fail. It is difficult to meet the power supply needs of new flexible and wearable electronic devices, limiting the industrial development of flexible zinc-ion batteries.
[0003] Therefore, there is an urgent need to provide a new zinc-ion battery mode to solve the above problems. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides an integrated flexible zinc ion battery with excellent electrochemical performance and deformation resistance.
[0005] The second aspect of the present invention provides a method for preparing an integrated flexible zinc ion battery.
[0006] The third aspect of the present invention provides an application of an integrated flexible zinc ion battery.
[0007] According to a first aspect of the present invention, an integrated flexible zinc ion battery is provided, wherein the zinc ion battery comprises an electrolyte layer, and electrode layers are respectively arranged on both sides of the electrolyte layer;
[0008] Wherein, the electrolyte layer and the electrode layer both contain acrylamide / N-hydroxymethyl acrylamide copolymer, and the acrylamide / N-hydroxymethyl acrylamide copolymer is copolymerized by acrylamide and N-hydroxymethyl acrylamide monomers and an initiator.
[0009] The zinc ion battery according to the first embodiment of the present invention has at least the following beneficial effects:
[0010] The present invention proposes a new zinc ion battery mode, using acrylamide / N-hydroxymethyl acrylamide copolymer as a matrix material, and synthesizing it by free radical copolymerization with an initiator, so as to build a cross-linked acrylamide / N-hydroxymethyl acrylamide copolymer network, eliminate the obvious interface between the original layers, and strengthen the interface between the electrode layer and the electrolyte layer, and penetrate the electrode layer and the electrolyte layer to form an all-in-one structure. Compared with the weak physical bonding between the electrode layer and the electrolyte layer of the traditional zinc ion battery, the interaction force between the electrode layer and the electrolyte layer interface of the present invention is a strong chemical cross-linking, so that the zinc ion battery structure of the present invention is more closely and thoroughly integrated, and the zinc ion battery of the present invention can effectively maintain structural stability in large-angle and long-term bending and twisting deformation, and avoid the interface debonding and misalignment of the positive electrode / electrolyte / negative electrode, thereby showing ultra-high deformation resistance.
[0011] The present invention adopts a homogenization strategy of constructing the electrode layer and the electrolyte layer with the same matrix, and utilizes the good compatibility between the same matrix materials to enhance the interface compatibility of the positive electrode / electrolyte / negative electrode. Compared with the traditional positive electrode / electrolyte / negative electrode prepared with different matrix materials, the interface contact area of the positive electrode / electrolyte / negative electrode can be increased, the interface contact resistance can be reduced, and thus the electrochemical performance can be improved.
[0012] According to some embodiments of the present invention, the electrode layer further contains a conductive material, a positive electrode active material, a negative electrode active material, and a surfactant.
[0013] According to some embodiments of the present invention, the conductive material is selected from at least one of carbon nanotubes, graphene, porous carbon, carbon black or carbon fiber.
[0014] According to some embodiments of the present invention, the mass ratio of the conductive material to the acrylamide / N-hydroxymethyl acrylamide copolymer is 0.25 to 4:1.
[0015] According to some embodiments of the present invention, the positive electrode active material includes at least one of a manganese-based compound, a vanadium-based compound and a Prussian blue analogue.
[0016] According to some embodiments of the present invention, the manganese-based compound includes at least one of MnO, Mn3O4, Mn2O3, and MnO2.
[0017] According to some embodiments of the present invention, the vanadium-based compound includes at least one of an oxide, a vanadate and a vanadium-based sulfide.
[0018] According to some embodiments of the present invention, the vanadium-based oxide includes at least one of V2O5 and VO2.
[0019] According to some embodiments of the present invention, the vanadate includes at least one of Zn2V2O7 and LiV3O8.
[0020] According to some embodiments of the present invention, the vanadium-based sulfide includes at least one of VS2 and V2S3.
[0021] According to some embodiments of the present invention, the mass ratio of the conductive material to the positive electrode active material of the positive electrode material is 0.1 to 2:1.
[0022] According to some embodiments of the present invention, the negative electrode active material includes selenide and zinc powder.
[0023] According to some embodiments of the present invention, the selenide includes at least one of copper selenide, silver selenide, zinc selenide or iron selenide.
[0024] According to some embodiments of the present invention, the mass ratio of the conductive material to the negative electrode active material of the negative electrode material is 1 to 10:1.
[0025] According to some embodiments of the present invention, the mass ratio of copper selenide to zinc powder in the active material of the flexible negative electrode material is 0.5 to 2:1.
[0026] According to some embodiments of the invention, the surfactant includes at least one of Triton, polyethylene glycol-p-isooctylphenyl ether, sodium dodecylbenzene sulfonate or sodium octadecyl sulfate.
[0027] According to another aspect of the present invention, a method for preparing the above-mentioned zinc ion battery is provided, comprising the following steps:
[0028] S1, dissolving acrylamide and N-hydroxymethyl acrylamide monomers, adding an initiator, dialyzing and freeze-drying to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer, and dissolving the copolymer to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer solution;
[0029] S2, preparing a negative electrode material from the acrylamide / N-hydroxymethyl acrylamide copolymer solution obtained in step S1, a conductive material, a negative electrode active substance and a surfactant;
[0030] S3, preparing a positive electrode material from the acrylamide / N-hydroxymethyl acrylamide copolymer solution obtained in step S1, a conductive material, a positive electrode active substance and a surfactant;
[0031] S4, evaporating and drying the acrylamide / N-hydroxymethyl acrylamide copolymer solution obtained in step S1 to prepare an electrolyte film;
[0032] S5, extruding and fusing the positive electrode material, the negative electrode material and the electrolyte film in sequence, heating and cross-linking to form an integrated zinc ion battery structure, and placing the structure in an electrolyte to obtain the zinc ion battery.
[0033] The preparation method according to the second aspect of the present invention has at least the following beneficial effects:
[0034] The preparation process of the scheme of the present invention is simple to operate and has good industrial application prospects.
[0035] The acrylamide / N-hydroxymethyl acrylamide copolymer is prepared by free radical copolymerization using acrylamide and N-hydroxymethyl acrylamide as monomers and ammonium persulfate and sodium pyrosulfite as initiators, and has the property of thermal self-crosslinking. The operation of obtaining the acrylamide / N-hydroxymethyl acrylamide copolymer is simple.
[0036] The mechanism of the present invention is that the flexible positive electrode material, the electrolyte and the flexible negative electrode material all contain acrylamide / N-hydroxymethyl acrylamide copolymer, and the acrylamide / N-hydroxymethyl acrylamide copolymer undergoes a heating cross-linking reaction. During the heating process, two adjacent hydroxymethyl functional groups undergo a dehydration reaction to form a methylene ether bond and a formaldehyde removal reaction to form a methylene group, thereby forming a cross-linked acrylamide / N-hydroxymethyl acrylamide copolymer network that runs through the flexible positive electrode material, the electrolyte and the flexible negative electrode material, eliminating the interface between the original flexible positive electrode material, the electrolyte and the flexible negative electrode material, and forming an integrated flexible zinc ion battery with an integrated structure of a three-in-one flexible positive electrode material, an electrolyte and a flexible negative electrode material.
[0037] According to some embodiments of the present invention, in step S1, the number average molecular weight of the acrylamide / N-hydroxymethyl acrylamide copolymer is 10,000 to 50,000.
[0038] According to some embodiments of the present invention, in step S1, the molecular weight distribution coefficient of the acrylamide / N-hydroxymethyl acrylamide copolymer is 1-4.
[0039] According to some embodiments of the present invention, in step S1, the molar ratio of acrylamide to N-hydroxymethyl acrylamide is 3:1 to 15:1.
[0040] The content of methylol groups in the acrylamide / N-hydroxymethyl acrylamide copolymer can be better controlled by controlling the monomer molar ratio, thereby controlling the crosslinking degree and liquid absorption rate.
[0041] According to some embodiments of the present invention, in step S1, the preparation process of the acrylamide / N-hydroxymethyl acrylamide copolymer solution specifically includes: dissolving acrylamide and N-hydroxymethyl acrylamide, adding an initiator to react under an inert atmosphere, performing dialysis and freeze-drying treatment to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer, and dissolving the copolymer to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer solution.
[0042] In order to prevent the acrylamide / N-hydroxymethyl acrylamide copolymer from slowly cross-linking at room temperature, the acrylamide / N-hydroxymethyl acrylamide copolymer is redissolved to prepare an acrylamide / N-hydroxymethyl acrylamide copolymer solution and stored at low temperature.
[0043] According to some embodiments of the present invention, in step S1, the initiator is ammonium persulfate and sodium pyrosulfite.
[0044] According to some embodiments of the present invention, in step S1, the molar ratio of ammonium persulfate to sodium metabisulfite is 1:1-2.
[0045] Preferably, in step S1, the molar ratio of ammonium persulfate to sodium metabisulfite is 1:1.
[0046] According to some embodiments of the present invention, in step S1, the molar ratio of the initiator to the acrylamide and N-hydroxymethyl acrylamide monomers is 1 to 2:500.
[0047] Preferably, in step S1, the molar ratio of the initiator to the acrylamide and N-hydroxymethyl acrylamide monomers is 2:500.
[0048] According to some embodiments of the present invention, in step S1, the concentration of the acrylamide / N-hydroxymethyl acrylamide copolymer solution is 1 to 10 wt %.
[0049] According to some embodiments of the present invention, in steps S2 and S3, the conductive material is selected from at least one of carbon nanotubes (MWNT), graphene, porous carbon, carbon black or carbon fiber.
[0050] According to some embodiments of the present invention, in steps S2 and S3, the mass ratio of the conductive material to the acrylamide / N-hydroxymethyl acrylamide copolymer is 0.25 to 4:1.
[0051] According to some embodiments of the present invention, in step S2, the preparation process of the negative electrode material specifically includes dispersing an acrylamide / N-hydroxymethyl acrylamide copolymer solution, a conductive material, a negative electrode active substance, and a surfactant in deionized water to obtain a dispersion, and then removing the deionized water.
[0052] According to some embodiments of the present invention, in step S2, the negative electrode active material includes selenide and zinc powder.
[0053] According to some embodiments of the present invention, the selenide includes at least one of copper selenide, silver selenide, zinc selenide or iron selenide.
[0054] According to some embodiments of the present invention, the mass ratio of copper selenide to zinc powder in the negative electrode active material is 0.5 to 2:1.
[0055] According to some embodiments of the present invention, in step S2, the mass ratio of the conductive material to the negative electrode active material is 1 to 10:1.
[0056] According to some embodiments of the present invention, the raw materials for preparing the negative electrode material also include a surfactant.
[0057] According to some embodiments of the invention, the surfactant includes at least one of Triton, polyethylene glycol-p-isooctylphenyl ether, sodium dodecylbenzene sulfonate or sodium octadecyl sulfate.
[0058] According to some embodiments of the present invention, in step S2, the mass ratio of the surfactant to deionized water is 1:50 to 10000.
[0059] According to some embodiments of the present invention, in step S3, the preparation process of the positive electrode material specifically includes dispersing an acrylamide / N-hydroxymethyl acrylamide copolymer solution, a conductive material, a positive electrode active substance, and a surfactant in deionized water to obtain a dispersion, and then removing the deionized water.
[0060] According to some embodiments of the present invention, in step S3, the positive electrode active material includes at least one of a manganese-based compound, a vanadium-based compound and a Prussian blue analogue.
[0061] According to some embodiments of the present invention, the manganese-based compound includes at least one of MnO, Mn3O4, Mn2O3, and MnO2.
[0062] According to some embodiments of the present invention, the vanadium-based compound includes at least one of an oxide, a vanadate and a vanadium-based sulfide.
[0063] According to some embodiments of the present invention, the vanadium-based oxide includes at least one of V2O5 and VO2.
[0064] According to some embodiments of the present invention, the vanadate includes at least one of Zn2V2O7 and LiV3O8.
[0065] According to some embodiments of the present invention, the vanadium-based sulfide includes at least one of VS2 and V2S3.
[0066] According to some embodiments of the present invention, in step S3, the mass ratio of the conductive material to the positive electrode active material is 0.1 to 2:1.
[0067] According to some embodiments of the present invention, in steps S2 and S3, the acrylamide / N-hydroxymethyl acrylamide copolymer, the conductive material, the positive and negative electrode active substances, and the surfactant are dispersed in deionized water by stirring and ultrasound.
[0068] According to some embodiments of the present invention, in steps S2 and S3, the stirring speed is 300-1000 rpm.
[0069] According to some embodiments of the present invention, in steps S2 and S3, the stirring time is 30 to 300 minutes.
[0070] According to some embodiments of the present invention, in steps S2 and S3, the ultrasonication time is 30 to 300 minutes.
[0071] According to some embodiments of the present invention, in step S4, the method of removing deionized water is natural evaporation at room temperature, the temperature being 20-40°C.
[0072] According to some embodiments of the present invention, in step S5, the cross-linking condition satisfies at least one of the following:
[0073] The cross-linking temperature is 50-200°C, and the cross-linking time is 0.5-10h.
[0074] Preferably, the cross-linking temperature is 90-120° C.; the cross-linking time is 1-5 hours.
[0075] According to some embodiments of the present invention, in step S5, the formation of the integrated zinc ion battery structure includes: firstly extruding and fusing the positive electrode material, the electrolyte film and the negative electrode material in sequence, and then performing a heating and cross-linking treatment.
[0076] According to some embodiments of the present invention, in step S5, the electrolyte includes at least one of aqueous solutions of inorganic zinc salts such as zinc nitrate, zinc chloride, zinc sulfate, manganese sulfate, and manganese acetate.
[0077] Preferably, the electrolyte comprises manganese sulfate and manganese acetate.
[0078] According to some embodiments of the present invention, in step S5, the concentration of the solute in the electrolyte is 0.1-4M.
[0079] According to another aspect of the present invention, a flexible electronic device or a wearable electronic device is provided, comprising the above-mentioned zinc ion battery.
[0080] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0081] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0083] Figure 1 The ultra-depth-of-field three-dimensional microscope images of the zinc ion batteries prepared in Comparative Examples 3 and 4 and Example 1 of the present invention, wherein a is Comparative Example 4, b is Comparative Example 3, and c is Example 1;
[0084] Figure 2 The ultra-depth-of-field three-dimensional microscope images of the zinc ion batteries prepared in Examples 1 to 4 of the present invention, wherein a is Example 1, b is Example 2, c is Example 3, and d is Example 4;
[0085] Figure 3 This is a super-depth three-dimensional microscope image of the interface structure of the zinc ion battery prepared in Example 2 of the present invention before and after being bent 180° 6000 times, wherein a is the interface structure when bent 180°, and b is the interface structure after being bent 180° 6000 times;
[0086] Figure 4 The ultra-depth-of-field three-dimensional microscope image of the interface structure of the zinc ion battery prepared in Example 2 of the present invention before and after being twisted 40° 3000 times, wherein a is the interface structure when twisted 40°, and b is the interface structure after being twisted 40° 3000 times;
[0087] Figure 5 The impedance comparison diagram of the zinc ion batteries prepared in Example 1 of the present invention and Comparative Examples 3 and 4;
[0088] Figure 6 This is a comparison diagram of the impedance of the zinc ion batteries prepared in Examples 1 to 4 of the present invention;
[0089] Figure 7 This is an impedance comparison diagram of the zinc ion battery prepared in Example 2 of the present invention before and after being bent 180° 6000 times;
[0090] Figure 8This is an impedance comparison diagram of the zinc ion battery prepared in Example 2 of the present invention before and after being bent 40° 3000 times;
[0091] Fig. 9 The figure is a bending resistance performance diagram of the zinc ion battery prepared in Example 1 of the present invention, wherein a is a cyclic voltammetry curve of Example 1 when the bending angles are 0°, 90°, 180°, and restored to 0°, and b is a cyclic voltammetry curve of Example 1 after repeated bending between 0° and 180° for 1 time, 2000 times, 4000 times, and 6000 times;
[0092] Fig.10 The figure is a bending resistance performance diagram of the zinc ion battery prepared in Example 1 of the present invention, wherein a is a cyclic voltammetry curve of Example 1 when the reversal angle is 0°, 20°, 40°, and restored to 0°, and b is a cyclic voltammetry curve of Example 1 after repeatedly twisting between 0° and 40° for 1 time, 1000 times, 2000 times, and 3000 times;
[0093] Fig.11 The charge and discharge voltage-capacity curves and the capacity retention rate variation diagram of the zinc ion battery prepared in Example 1 of the present invention after being repeatedly bent between 0° and 180° for 1 time, 2000 times, 4000 times, and 6000 times;
[0094] Fig.12 The charge and discharge voltage-capacity curves and the capacity retention rate variation diagram of the zinc ion battery prepared in Example 1 of the present invention after being repeatedly twisted between 0° and 40° for 1 time, 1000 times, 2000 times, and 3000 times;
[0095] Fig.13 The rate performance graph and charge-discharge voltage-capacity curve graph of the zinc ion battery prepared in Example 1 and Comparative Examples 1 and 2 of the present invention, wherein a is the rate performance graph of the zinc ion battery, and b is the charge-discharge voltage-capacity curve graph of the zinc ion battery at 1 mA / cm 2 The charge and discharge voltage-capacity curve under current density;
[0096] Fig.14 The figure is a comparison of the cycle stability of the zinc ion batteries prepared in Example 1 of the present invention and Comparative Examples 1 and 2;
[0097] Fig.15 The rate performance graph and charge-discharge voltage-capacity curve of the zinc ion battery prepared in Example 1 and Comparative Examples 3 and 4 of the present invention, wherein a is the rate performance graph of the zinc ion battery, and b is the charge-discharge voltage-capacity curve of the zinc ion battery at 1 mA / cm 2 The charge and discharge voltage-capacity curve under current density;
[0098] Fig.16Figures of two zinc ion batteries prepared in Example 1 of the present invention connected in series and lighting an LED lamp in the flat b, bent c, and twisted d states, as well as the charge and discharge voltage-capacity curve of the zinc ion battery prepared in Example 1 and the charge and discharge voltage-capacity curve a of two batteries connected in series and parallel. DETAILED DESCRIPTION
[0099] The embodiments of the present invention are described in detail below, and the same or similar reference numerals throughout the embodiments represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0100] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0101] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0102] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0103] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0104] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0105] Acrylamide: Greagent Reagent Company, 79-06-1;
[0106] N-hydroxymethyl acrylamide: Titan Corporation, 924-42-5;
[0107] Ammonium persulfate: Aladdin Reagent Company, 7727-54-0;
[0108] Sodium metabisulfite: Greagent Reagent Company, 7681-57-4;
[0109] Triton X-100: Aladdin Reagent Company, 9002-93-1;
[0110] MWNT, NANOCYL NC7000, 308068-56-6;
[0111] CuSe: Homemade, (1) Add 1.35 mol NaOH and 0.006 mol Se powder to 120 mL deionized water, and the NaOH dissolved in water undergoes an exothermic reaction until Se is completely dissolved. (2) Dissolve 0.0078 mol Cu(Ac)2·2H2O in 45 mL EDTA2Na aqueous solution (0.2 M) to obtain a mixed solution. (4) Slowly add the mixed solution to the alkali selenium aqueous solution and stir rapidly to produce a large amount of black precipitate. (5) Filter the product, rinse with distilled water, and dry at 60°C for 6 hours to obtain CuSe.
[0112] ZnSO4: Aladdin Reagent Company, 7733-02-0;
[0113] MnSO4: Aladdin Reagent Company, 7785-87-7.
[0114] Example 1
[0115] The present embodiment provides an integrated flexible zinc ion battery, comprising a positive electrode, an electrolyte layer and a negative electrode arranged in sequence; the electrolyte layer and the positive and negative electrode layers all contain acrylamide / N-hydroxymethyl acrylamide copolymer.
[0116] The raw materials for preparing the positive and negative electrode layers include acrylamide / N-hydroxymethyl acrylamide copolymer, conductive materials, positive and negative electrode active substances and surfactants; the raw materials for preparing the electrolyte layer include acrylamide / N-hydroxymethyl acrylamide copolymer. The positive electrode / electrolyte / negative electrode are fused by extrusion, and the acrylamide / N-hydroxymethyl acrylamide copolymer therein can undergo a thermal cross-linking reaction to form a cross-linked copolymer network that runs through the positive electrode / electrolyte / negative electrode, eliminating the original obvious interface between the layers.
[0117] This embodiment also provides a method for preparing the above-mentioned integrated flexible zinc ion battery, and the specific preparation method is as follows:
[0118] S1, acrylamide and N-hydroxymethyl acrylamide were added to 60mL deionized water, stirred for 10min to dissolve, and nitrogen was passed to deoxygenate to obtain solution A; ammonium persulfate was then dissolved in 10mL deionized water, and slowly added dropwise to solution A under stirring and nitrogen flow to obtain solution B; sodium pyrosulfite was then dissolved in 10mL deionized water, and slowly added dropwise to solution B under stirring and nitrogen flow; the reaction was carried out at room temperature for 24h under nitrogen protection, the product was poured into a dialysis bag (molecular weight cutoff 14000), and dialyzed with deionized water for 72h, with the water being changed every 12 hours; the dialyzed product was freeze-dried to obtain a white flocculent solid, and in order to prevent the acrylamide / N-hydroxymethyl acrylamide copolymer from slowly crosslinking at room temperature, the acrylamide / N-hydroxymethyl acrylamide copolymer was redissolved in deionized water to prepare a 5wt% acrylamide / N-hydroxymethyl acrylamide copolymer solution and stored at low temperature.
[0119] S2, add 0.4gCuSe to a 150mL beaker, then add deionized water and stir rapidly for 30min to form a CuSe dispersion; add 0.05mL surfactant Triton X-100, disperse 0.2gMWNT in the CuSe dispersion by ultrasonic stirring to form a MWNT / CuSe dispersion; then add 1g of 5% acrylamide / N-hydroxymethyl acrylamide copolymer solution, stir in an ice-water bath and perform ultrasonic dispersion treatment for 60min to obtain a CuSe / MWNT / acrylamide / N-hydroxymethyl acrylamide copolymer dispersion; finally, pour 0.35gZn powder into the high-speed stirring CuSe / MWNT / acrylamide / N-hydroxymethyl acrylamide copolymer dispersion, stir for 5min and pour into a pre-prepared mold; volatilize at room temperature to form a film to prepare a 40% amount of MWNT / acrylamide / N-hydroxymethyl acrylamide copolymer / Zn flexible negative electrode material; cut it into 2*1cm electrodes for use.
[0120] S3. After adding 0.05 mL of surfactant Triton X-100, 0.4 g of MWNT was dispersed in deionized water by ultrasonic stirring for 30 min to form a MWNT dispersion; 8 g of 5% acrylamide / N-hydroxymethyl acrylamide copolymer solution was added, and ultrasonic stirring was performed in an ice-water bath for 60 min to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer / MWNT suspension; 0.2667 g of ultra-long MnO2 nanowires were added, and ultrasonic stirring was performed in an ice-water bath for 30 min to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer / MWNT / MnO2 suspension; the acrylamide / N-hydroxymethyl acrylamide copolymer / MWNT / MnO2 suspension was poured into a pre-prepared polytetrafluoroethylene mold, and volatilized at room temperature to form a film to prepare an acrylamide / N-hydroxymethyl acrylamide copolymer / MWNT / MnO2 flexible positive electrode material with 25% MnO2.
[0121] S4. Mix 1.5 g of acrylamide / N-hydroxymethylacrylamide copolymer and 60 mL of deionized water, and then stir them at 300 r / min for 120 min using a mechanical stirrer to obtain an acrylamide / N-hydroxymethylacrylamide copolymer solution. Then pour the acrylamide / N-hydroxymethylacrylamide copolymer solution into a mold, and wait for the solvent to evaporate to obtain an acrylamide / N-hydroxymethylacrylamide copolymer film.
[0122] S5. The pre-cut acrylamide / N-hydroxymethyl acrylamide copolymer electrolyte is humidified with deionized water for 3 minutes and then clamped between the flexible positive electrode material and the flexible negative electrode material; the bubbles between the positive electrode / electrolyte / negative electrode are squeezed out to make the positive electrode / electrolyte / negative electrode tightly bonded; the positive electrode / electrolyte / negative electrode sandwich structure is pressed under a weight of 500g for 8 hours and then taken out, and the deionized water is evaporated at room temperature; then it is transferred to a vacuum oven at 110℃ and heated for cross-linking for 3 hours to obtain an integrated flexible zinc ion battery.
[0123] S6. Place the integrated symmetrical battery in 2M ZnSO4+0.1M MnSO4 electrolyte and fully immerse it for 3 minutes; cut the carbon cloth into long strips and connect them to the positive and negative electrodes respectively, and use a sealing machine to encapsulate the battery with heat shrink film. The contact points between the carbon cloth and the positive and negative electrodes need to be heat-sealed in particular to ensure that the carbon cloth is tightly bonded to the positive and negative electrodes.
[0124] Example 2
[0125] This embodiment prepares an integrated flexible zinc ion battery, which differs from Embodiment 1 in that the heating cross-linking time in step S5 is 2 hours.
[0126] Example 3
[0127] This embodiment prepares an integrated flexible zinc ion battery, which differs from Embodiment 1 in that the heating cross-linking time in step S5 is 4 hours.
[0128] Example 4
[0129] This embodiment prepares an integrated flexible zinc ion battery, which differs from Embodiment 1 in that the heating cross-linking time in step S5 is 5 hours.
[0130] Comparative Example 1
[0131] This comparative example prepares an integrated flexible zinc ion battery, which differs from Example 1 in that the mass fraction of copper selenide in the copper selenide flexible negative electrode material in step S2 is 50%.
[0132] Comparative Example 2
[0133] This comparative example prepares an integrated flexible zinc ion battery, which differs from Example 1 in that the mass fraction of copper selenide in the copper selenide flexible negative electrode material in step S2 is 60%.
[0134] Comparative Example 3
[0135] In this comparative example, a flexible zinc ion battery is prepared, which differs from Example 1 in that: step S5 does not perform heating cross-linking, and the flexible positive and negative electrode materials and the acrylamide / N-hydroxymethyl acrylamide copolymer in the electrolyte are in a gel state after absorbing the electrolyte.
[0136] Comparative Example 4
[0137] In this comparative example, a flexible zinc ion battery is prepared, which differs from Example 1 in that: in step S5, after the flexible positive and negative electrode materials and the electrolyte are heated and cross-linked, they are stacked layer by layer to form an electrode|electrolyte|electrode sandwich structure.
[0138] Test example
[0139] This test example tests the structure and performance of the zinc ion battery prepared in the embodiment and the comparative example.
[0140] 1) Morphology and structure test:
[0141] The cross-section of the zinc ion battery prepared in the embodiment and the comparative example was observed by using an ultra-depth 3D microscope to observe the morphology of the electrode|electrolyte|electrode interface. The results of embodiment 1 and comparative examples 3 and 4 are as follows: Figure 1 (Group a is Comparative Example 4, Group b is Comparative Example 3, and Group c is Example 1). Among them, Comparative Example 4 is a sandwich structure flexible zinc ion battery, and Comparative Example 3 is a gel-state flexible zinc ion battery. There are obvious interfaces and interface transition regions between the positive electrode / electrolyte / negative electrode, while the positive electrode / electrolyte / negative electrode of the integrated flexible zinc ion battery has no interface and has been fused into an integrated structure. The sharp contrast confirms that the integration of the positive electrode / electrolyte / negative electrode of a flexible zinc ion battery can be achieved through the thermal crosslinking of acrylamide / N-hydroxymethyl acrylamide copolymers. The cross-sections of the zinc ion batteries prepared in Examples 1 to 4 were subjected to morphological observations of the electrode|electrolyte|electrode interface. The results of Examples 1 to 4 are shown in FIG. Figure 2 (Group b is Example 1, Group a is Example 2, Group c is Example 3, and Group d is Example 4) As shown, as the cross-linking time increases from 2h to 5h, the interface structure of the integrated flexible zinc ion battery shows no interface and has been fused into an integrated structure, indicating that the cross-linking time has little effect on the integrated interface structure of the integrated flexible zinc ion battery. The integrated zinc ion battery prepared in Example 1 was subjected to bending and twisting deformation tests. Figure 3 As shown, compared with the interface structure before bending Figure 3a and the interface structure after bending 180° for 6000 times Figure 3 b It can be found that the seamless integrated structure of the integrated flexible zinc-ion battery can be well maintained, and there is no debonding at the positive electrode / electrolyte / negative electrode interface. Figure 4 As shown, compared with the interface structure before twisting Figure 4 a and the interface structure after twisting 40° for 3000 cycles Figure 4 b It can be found that the seamless integrated structure of the integrated flexible zinc-ion battery can be well maintained, and there is no debonding at the positive electrode / electrolyte / negative electrode interface.
[0142] 2) Performance test:
[0143] The electrochemical performance and impedance tests of the zinc ion batteries prepared in the examples and comparative examples were performed using an electrochemical workstation.
[0144] like Figure 5 As shown, Comparative Example 4 is a sandwich-structured flexible zinc-ion battery, and its interface charge transfer resistance is 91.62Ω, and Comparative Example 3 is a gel-state flexible zinc-ion battery, and its interface charge transfer resistance is 47.68Ω, which is significantly higher than the charge transfer resistance of 19.33Ω of the integrated flexible zinc-ion battery in Example 1, indicating that the integrated interface structure can effectively reduce the interface charge transfer resistance, which can also explain why the electrochemical performance of the integrated flexible zinc-ion battery is significantly better than that of the sandwich-structured flexible zinc-ion battery. Figure 6 It can be seen that the crosslinking time of the zinc ion batteries prepared in Example 1, Example 2, Example 3, and Example 4 is 3, 2, 4, and 5 h, and the interfacial charge transfer resistance is 12.71Ω, 32.65Ω, 43.78Ω, and 91.12Ω, respectively, indicating that with the increase of the crosslinking time, the interfacial charge transfer resistance also increases, which is related to the increase in the crosslinking time causing the increase in the degree of crosslinking of the molecular chains of the c-acrylamide / N-hydroxymethylacrylamide copolymer at the interface, resulting in a decrease in the electrophilicity.
[0145] The integrated flexible zinc-ion battery prepared in Example 1 was subjected to bending and twisting deformation tests using a flexible electronic tester in conjunction with an electrochemical work and blue battery test system, and its electrochemical performance was tested. The electrochemical impedance of the integrated flexible zinc-ion battery in Example 1 before and after bending 180° for 6000 times was tested. Figure 7 It can be seen that after the integrated flexible zinc ion battery was bent 6000 times, the interfacial charge transfer resistance only increased from the initial 3.60Ω to 4.53Ω. Figure 8 It can be seen that after the integrated flexible zinc-ion battery was bent 6000 times, the interfacial charge transfer resistance only increased from the initial 1.47Ω to 2.32Ω.
[0146] like Fig. 9 and Fig.10 As shown. Fig.10 (a is the cyclic voltammetry curve when bent from 0° to 90° and 180°, and b is the cyclic voltammetry curve before and after repeated bending between 0° and 180° for 6000 times) It can be seen that the integrated flexible zinc ion battery prepared in Example 1 has basically no change in specific capacitance when bent from 0° to 90° and 180°, and the capacitance retention can reach 101% after repeated bending between 0° and 180° for 6000 times. Fig.11 (a is the cyclic voltammetry curve from 0° to 20° and 40°, b is the cyclic voltammetry curve before and after repeated twisting between 0° and 40° for 3000 times) It can be seen that the cyclic voltammetry curve of the integrated flexible zinc ion battery prepared in Example 1 is basically unchanged when twisted from 0° to 20°, 40° and 60°, and the capacity can be retained up to 100% after repeated twisting between 0° and 40° for 50,000 times. The results show that the integrated flexible zinc ion battery prepared by the present invention has excellent bending and twisting deformation resistance. Fig.11 As shown in the figure, the integrated flexible zinc ion battery prepared in Example 1 can maintain a capacity of 100.6% after being bent repeatedly between 0° and 180° for 6000 times. Fig.12 As shown, after the integrated flexible zinc ion battery prepared in Example 1 was repeatedly twisted between 0° and 40° for 3000 times, the capacity retention rate of the integrated flexible zinc ion battery could reach 99.1%.
[0147] The rate performance of integrated flexible zinc-ion batteries with different CuSe dosages was tested. Fig.12 As shown inside, when the current density is 0.1, 0.2, 0.3, 0.5 and 1 mA / cm 2 When the area specific capacity of the integrated flexible zinc ion battery of Example 1 is 0.079, 0.078, 0.078, 0.072 and 0.066 mAh / cm 2 The area specific capacities of the integrated flexible zinc ion battery of comparative example 1 are 0.099, 0.091, 0.081, 0.071 and 0.060 mAh / cm 2 The area specific capacities of the integrated flexible zinc ion battery in comparative example 2 are 0.109, 0.106, 0.092, 0.083 and 0.066 mAh / cm 2 ; at 1mA / cm 2 After 5 cycles of high charge and discharge rate, immediately set the charge and discharge rate back to 0.1 mA / cm 2 It was found that the area specific capacities of the integrated flexible zinc ion batteries prepared in Comparative Examples 2, 1 and Example 1 were 0.090, 0.091 and 0.111 mAh / cm2 It can be seen that when the CuSe content increases from 40wt% to 60wt%, the rate performance of the integrated flexible zinc-ion battery decreases significantly. Fig.12 As shown outside, at a higher current density, the area specific capacity of the integrated flexible zinc ion battery prepared in Example 1 and Comparative Examples 1 and 2 are 0.065, 0.06 and 0.57 mAh / cm, respectively. 2 It can be found that at higher current density, as the amount of copper selenide increases, the area specific capacity of the integrated battery also shows a downward trend.
[0148] Then the cycling stability of the integrated flexible zinc-ion battery with different CuSe dosages was tested. Fig.14 It can be seen that the area specific capacity of the integrated flexible zinc ion prepared in Example 1 always shows an increasing trend during the 500 cycles of the battery, and the area specific capacity increases from 0.06 mAh / cm2 to 0.137 mAh / cm 2 The capacity retention rate is 228.3%. The increase in specific capacity may be due to the gradual activation of the integrated flexible zinc-ion battery during the charge and discharge process, showing good cycle stability. Similarly, the area specific capacity of the integrated flexible zinc-ion battery prepared in Comparative Example 1 always shows an increasing trend during the 500 cycles, and the area specific capacity starts to rise from 0.08 mAh / cm2 and finally stabilizes at 0.11 mAh / cm 2 , the capacity retention rate is 137.5%. However, the area specific capacity of the integrated flexible zinc ion battery prepared according to Comparative Example 2 decreased significantly during the 500 cycles, and the area specific capacity decreased from 0.11 mAh / cm 2 Down to 0.048 mAh / cm 2 , the capacity retention rate is 43.6%.
[0149] According to the data analysis of comprehensive rate performance and cycle stability, the integrated flexible zinc ion battery prepared in Example 1 has good rate performance and ultra-high cycle stability.
[0150] like Fig.15 As shown in a, according to the rate performance of the zinc ion battery prepared in Example 1 and Comparative Examples 3 and 4, it can be found that the rate performance of the integrated flexible zinc ion battery is better than that of the gel zinc ion battery and the sandwich structure zinc ion battery. Fig.15 As shown in b, the zinc ion batteries prepared according to Example 1 and Comparative Examples 3 and 4 have a 2 At the current density, the area specific capacity of the integrated flexible zinc ion battery prepared in Example 1 and Comparative Examples 3 and 4 is 0.020, 0.061 and 0.071 mAh / cm, respectively. 2 ,
[0151] like Fig.16 As shown, the two integrated flexible zinc ion batteries prepared in Example 1 connected in series can light up the LED lamp in the flat, bent and twisted states, indicating that the integrated flexible zinc ion battery prepared by the present invention has broad application prospects in new flexible electronic devices.
[0152] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. An integrated flexible zinc ion battery, characterized in that: The zinc ion battery comprises an electrolyte layer, and electrode layers are respectively arranged on both sides of the electrolyte layer; Wherein, the electrolyte layer and the electrode layer both contain acrylamide / N-hydroxymethyl acrylamide copolymer, and the acrylamide / N-hydroxymethyl acrylamide copolymer is copolymerized from acrylamide and N-hydroxymethyl acrylamide monomers.
2. A method for preparing a zinc ion battery as claimed in claim 1, characterized in that: The steps include: S1, dissolving acrylamide and N-hydroxymethyl acrylamide monomers, adding an initiator, dialyzing and freeze-drying to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer, and dissolving the copolymer to obtain an acrylamide / N-hydroxymethyl acrylamide copolymer solution; S2, preparing a negative electrode material from the acrylamide / N-hydroxymethyl acrylamide copolymer solution obtained in step S1, a conductive material, a negative electrode active substance and a surfactant; S3, preparing a positive electrode material from the acrylamide / N-hydroxymethyl acrylamide copolymer solution obtained in step S1, a conductive material, a positive electrode active substance and a surfactant; S4, evaporating and drying the acrylamide / N-hydroxymethyl acrylamide copolymer solution obtained in step S1 to prepare an electrolyte film; S5, extruding and fusing the positive electrode material, the electrolyte film and the negative electrode material in sequence, heating and cross-linking to form an integrated zinc ion battery structure, and placing the structure in an electrolyte to obtain the zinc ion battery.
3. The preparation method according to claim 2, characterized in that: In step S1, the number average molecular weight of the acrylamide / N-hydroxymethyl acrylamide copolymer is 10,000 to 50,000; and / or, in step S1, the molecular weight distribution coefficient of the acrylamide / N-hydroxymethyl acrylamide copolymer is 1 to 4; and / or, in step S1, the molar ratio of acrylamide to N-hydroxymethyl acrylamide is 3:1 to 15:
1.
4. The preparation method according to claim 2, characterized in that: In step S1, the initiator is ammonium persulfate and sodium pyrosulfite; and / or, in step S1, the molar ratio of the ammonium persulfate and sodium pyrosulfite is 1:1-2; and / or, in step S1, the molar ratio of the initiator to the acrylamide and N-hydroxymethyl acrylamide monomer is 1-2:500; and / or, in step S1, the concentration of the acrylamide / N-hydroxymethyl acrylamide copolymer solution is 1-10wt%.
5. The preparation method according to claim 2, characterized in that: In steps S2 and S3, the conductive material is selected from at least one of carbon nanotubes, graphene, porous carbon, carbon black or carbon fiber; and / or, in steps S2 and S3, the mass ratio of the conductive material to the acrylamide / N-hydroxymethyl acrylamide copolymer is 0.25 to 4:
1.
6. The preparation method according to claim 2, characterized in that: In step S2, the negative electrode active material includes selenide and zinc powder; and / or, the selenide includes at least one of copper selenide, silver selenide, zinc selenide or iron selenide; and / or, the mass ratio of the selenide to the zinc powder is 0.5 to 2:1; and / or, in step S2, the mass ratio of the conductive material to the negative electrode active material is 1 to 10:
1.
7. The preparation method according to claim 2, characterized in that: In step S3, the positive electrode active material includes at least one of a manganese-based compound, a vanadium-based compound and a Prussian blue analogue; and / or, in step S3, the mass ratio of the conductive material to the positive electrode active material is 0.1 to 2:
1.
8. The preparation method according to claim 2, characterized in that: In step S4, the temperature of the evaporation drying process is 20-40°C.
9. The preparation method according to claim 2, characterized in that: In step S5, the heating cross-linking condition satisfies at least one of the following: The cross-linking temperature is 50-200° C., and the cross-linking time is 0.5-10 h. Preferably, the cross-linking temperature is 90-120° C., and the cross-linking time is 1-5 h.
10. A flexible electronic device or a wearable electronic device, characterized in that: It comprises the integrated flexible zinc ion battery as claimed in claim 1 or the integrated flexible zinc ion battery prepared by the preparation method as claimed in any one of claims 2 to 9.